2021
DOI: 10.1038/s41598-021-81197-5
|View full text |Cite
|
Sign up to set email alerts
|

Risk of ambulance services associated with ambient temperature, fine particulate and its constituents

Abstract: Short-term adverse health effects of constituents of fine particles with aerodynamic diameters less than or equal to 2.5 μm (PM2.5) have been revealed. This study aimed to evaluate the real-time health outcome of ambulance services in association with ambient temperature and mass concentrations of total PM2.5 level and constituents in Kaohsiung City, an industrialized city with the worst air quality in Taiwan. Cumulative 6-day (lag0-5) relative risk (RR) and 95% confidence interval (CI) of daily ambulance serv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 41 publications
(84 reference statements)
0
10
0
Order By: Relevance
“…We reviewed the titles and the abstracts of 153 studies, of which 40 met our prespecified inclusion criteria. Most (23) were from East Asia [37,41,73,[86][87][88][89][90][91][92][93][94][95][96][97][98][99][100][101][102][103][104][105], 10 were from Europe [5,30,53,74,75,79,[106][107][108][109], 5 were from USA and Canada [110][111][112][113][114], and far fewer were included from the Pacific region [115], Latin America, and the Caribbean [116].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We reviewed the titles and the abstracts of 153 studies, of which 40 met our prespecified inclusion criteria. Most (23) were from East Asia [37,41,73,[86][87][88][89][90][91][92][93][94][95][96][97][98][99][100][101][102][103][104][105], 10 were from Europe [5,30,53,74,75,79,[106][107][108][109], 5 were from USA and Canada [110][111][112][113][114], and far fewer were included from the Pacific region [115], Latin America, and the Caribbean [116].…”
Section: Resultsmentioning
confidence: 99%
“…Most papers discussed all-cause and specific-cause mortality or morbidity, including respiratory outcomes. Of the identified papers, 24 discussed mortality from respiratory causes [5,53,[73][74][75]79,86,88,90,92,93,[95][96][97][98]100,[106][107][108][109][110][114][115][116], 14 incorporated respiratory emergency department visits and hospital admissions [30,41,87,89,91,94,99,[102][103][104][105][111][112][113], 1 was for ambulance calls for respiratory distress [101], and 1 was for lung cancer incidence [37]. The details of those studies are reported below, separately for respiratory morbidity and mortality and for heat wave episodes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From the academic point of view, there is a lack of EAS-related research on Taiwan. This can be demonstrated as follows: if we use the search query of “(ambulance) AND (weather OR temperature) AND (Taiwan OR Taipei)” to conduct a search of the most popular medical journals database, PubMed, only four publications can be found that investigate the relationship between weather and EAS demand in Taiwan ( 21 , 32 34 ). Hence, this study can further contribute to forming the building blocks of EAS and weather-related research for Taiwan.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, if more than one lag estimate was presented [15,[17][18][19][27][28][29] , the shortest lag in the study was selected to calculate the pooled OR [24,30] . The study that only provided cumulative lag (lag 0-5) was also used to determine overall risk estimates [31] .…”
Section: Data Synthesis and Statistical Analysismentioning
confidence: 99%